Penilaian Kinerja Jaringan Air Minum Pada Kawasan Permukiman di Desa Babulu Laut - Detantyo, Aria Jati; Pratomo, Rahmat Aris; Pratama, Maryo Inri; Syafitri, Elin Diyah (COMPACT: Spatial Development Journal, 2024)
Water is considered a fundamental requirement in the realm of human existence. The sixth goal of the Sustainable Development Goals (SDGs) focuses on ensuring accessibility and sustainable management of water for all sectors of society, especially within settlements. Babulu Laut is a clear example of a residential area that faces complex challenges related to the provision of basic needs such as drinking water. Researchers have assessed the drinking water network that is currently used by residents of Babulu Laut Village, especially in the research area, namely in RT 01, RT 02, RT 03, RT 05, RT 06, RT 07, RT 08. RT 09, RT 11, RT 16, RT 17, and RT 18 to identify drinking water problems in residential areas in Babulu Laut Village. This research used qualitative and quantitative analysis techniques, such as descriptive qualitative analysis of discourse and scoring model analysis with the aim of obtaining existing data related to the current users of the drinking water network in Babulu Laut Village and their needs. The findings of this study indicate that the drinking water network used by RTs in the research area in Babulu Laut Village currently includes rainwater, boreholes, and refill water, each of which has a classification of poor and bad performance.